ANALYSIS OF THE IMPACT OF BEFORE AND AFTER OVERHAUL ON THE THERMAL EFFICIENCY OF THE MUARA KARANG PLTG GAS TURBINE USING A SANKEY DIAGRAM - Hendri; Anugerah Banjarnahor; Muhammad Ridwan (Universitas Muhammadiyah Metro, 2026)
Gas turbine performance gradually degrades due to fouling, thermal stress, and component wear, leading to a reduction in thermal efficiency. Major overhaul is essential to restore performance close to design conditions. This study analyzes the impact of major overhaul on the thermal efficiency of Gas Turbine Unit 1.2 at Muara Karang Power Plant, focusing on maximum load operation at 90 MW. Actual operational data were processed using Brayton cycle thermodynamic principles to calculate net work output, fuel energy input, and overall thermal efficiency. Calculations were validated with Cycle Tempo and Engineering Equation Solver (EES), showing a deviation within 5%. Energy distribution and losses were visualized using Sankey diagrams to compare before and after overhaul conditions. Results indicate that thermal efficiency increased from 31.91% to 32.41% after overhaul, corresponding to a reduction in heat loss of approximately 2,950 kJ/s. The improvements were mainly associated with compressor recovery and reduced irreversibility in the combustor. These findings demonstrate that major overhaul is an effective maintenance strategy to improve thermal performance, while Sankey diagrams provide valuable insights into component-level energy losses for operational and maintenance decision-making.